The Holocaust & the exile of Yiddish: a history of the Algemeyne Entsiklopedye - Trachtenberg, Barry (Rutgers University Press, 2022)
"A Bible for the New Age": Berlin, 1930-1933 -- "Man Plans, and Hitler Laughs": Paris, 1933-1940 -- "Spinning the Historical Threads": New York, 1940-1966.